Association of Novel Streptococcus sanguinis Virulence Factors With Pathogenesis in a Native Valve Infective Endocarditis Model - Martini, Anthony M.; Moricz, Bridget S.; Ripperger, Allison K.; Tran, Phuong M.; Sharp, Molly E.; Forsythe, Ana N.; Kulhankova, Katarina; Salgado-Pabón, Wilmara; Jones, Bradley D. (Frontiers in Microbiology, 2020)
Streptococcus sanguinis (S. sanguinis) is an abundant oral commensal which can cause disseminated human infection if it gains access to the bloodstream. The most important among these diseases is infective endocarditis (IE). While virulence phenotypes of S. sanguinis have been correlated to disease severity, genetic factors mediating these phenotypes and contributing to pathogenesis are largely uncharacterized. In this report, we investigate the roles of 128 genes in virulence-related phenotypes of S. sanguinis and characterize the pathogenic potential of two selected mutants in a left-sided, native valve infective endocarditis rabbit model. Assays determining the ability of our mutant strains to produce a biofilm, bind to and aggregate platelets, and adhere to or invade endothelial cells identified sixteen genes with novel association to these phenotypes. These results suggest the presence of many uncharacterized genes involved in IE pathogenesis which may be relevant for disease progression. Two mutants identified by the above screening process – SSA_1099, encoding an RTX-like protein, and mur2, encoding a peptidoglycan hydrolase – were subsequently evaluated in vivo. Wild type (WT) S. sanguinis reliably induced cardiac vegetations, while the SSA_1099 and mur2 mutants produced either no vegetation or vegetations of small size. Splenomegaly was reduced in both mutant strains compared to WT, while pathology of other distal organs was indistinguishable. Histopathology analyses suggest the cardiac lesions and vegetations in this model resemble those observed in humans. These data indicate that SSA_1099 and mur2 encode virulence factors in S. sanguinis which are integral to pathogenesis of IE.